Video measurements of instantaneous forces of flapping wing vehicles. (December 2015) - Jennings, Alan; Mayhew, Michael; Black, Jonathan
Abstract: Flapping wings for small aerial vehicles have revolutionary potential for maneuverability and endurance. Ornithopters fail to achieve the performance of their biological equivalents, despite extensive research on how animals fly. Flapping wings produce peak forces due to the stroke reversal of the wing. This research demonstrates in-flight measurements of an ornithopter through the use of image processing, specifically measuring instantaneous forces. Results show that the oscillation about the flight path is significant, being about 20% of the mean velocity and up to 10 g׳s. Results match forces with deformations of the wing to contrast the timing and wing shape of the upstroke and the downstroke. Holding the vehicle fixed (e.g. wind tunnel testing or simulations) structural resonance is affected along with peak forces, also affecting lift. Non-contact, in-flight measurements are proposed as the best method for matching the flight conditions of flapping wing vehicles. Abstract : Graphical abstract: Abstract : Highlights: Instantaneous forces on a flapping wing are resolved using image processing. Locally weighted regression derivatives are employed to isolate periodic behavior. Small oscillations about the average path produce large forces (10×׳s its weight). Results show oscillation must be included in flapping wing test and simulation.